The curative effects of methylsulfonylmethane against glycerol-induced acute renal failure in rats - Shaza Anwar Al laham (Universidade de São Paulo, 2018)
Abstract The present study was performed to explore the curative effect of Methylsulfonylmethane (MSM) in an experimental model of myoglobinuric acute renal failure (ARF). In this experimental model, Rats were injected with 50% glycerol (10 mL/kg, im) followed by an hour later and daily in the next six days by MSM (400 mg/kg) or saline. Kidney's function (urea and creatinine), and reduced glutathione were analyzed. A renal failure produced by glycerol injection, with a significant increase of blood urea and serum creatinine was observed. Rats that received MSM in addition to glycerol had significantly lower blood urea and serum creatinine levels compared to those receiving glycerol alone. However, glutathione has markedly increased after MSM treatment. The effect is probably due to the antioxidant activity of MSM. This may provide therapeutic opportunities for treating humans, myoglobinuric ARF.